2019
DOI: 10.1097/bot.0000000000001553
|View full text |Cite
|
Sign up to set email alerts
|

Short Versus Long Cephalomedullary Nails for Pertrochanteric Hip Fractures: A Randomized Prospective Study

Abstract: Objective: To compare functional and clinical outcomes in patients with pertrochanteric hip fractures treated with either a short (SN) or long (LN) cephalomedullary nail. Design: Prospective, randomized. Setting: Clinical investigation was performed at the Mayo Clinic's Level 1 Trauma Center in Rochester, MN. Patients/Participants: Two hundred twenty patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 33 publications
5
57
1
Order By: Relevance
“…Shannon et al used the SF-36 instrument, with a power calculation predicated on the minimum clinically important difference for total knee replacement and tibial plateau fracture fixation. [21][22][23] This study also excluded patients with dementia on the basis of inability to complete the PROM, thereby substantially reducing the generalizability of the findings to a population with a high burden of cognitive impairment. It has been demonstrated that the EuroQol 5-dimension instrument (EQ-5D) can be effectively completed by carers or relatives with a high degree of reliability and, given that its effect size in hip fracture is relatively well-understood and it already forms part of the core outcome set in the United Kingdom for hip fracture research, it would represent a much more appropriate choice of PROM.…”
Section: Discussionmentioning
confidence: 99%
“…Shannon et al used the SF-36 instrument, with a power calculation predicated on the minimum clinically important difference for total knee replacement and tibial plateau fracture fixation. [21][22][23] This study also excluded patients with dementia on the basis of inability to complete the PROM, thereby substantially reducing the generalizability of the findings to a population with a high burden of cognitive impairment. It has been demonstrated that the EuroQol 5-dimension instrument (EQ-5D) can be effectively completed by carers or relatives with a high degree of reliability and, given that its effect size in hip fracture is relatively well-understood and it already forms part of the core outcome set in the United Kingdom for hip fracture research, it would represent a much more appropriate choice of PROM.…”
Section: Discussionmentioning
confidence: 99%
“…and Shannon et al . , had a randomised controlled trail (RCT) design 27 , 28 , 33 . The remaining thirteen studies were retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies included data on operative times for the surgical procedures. All but one study reporting a significantly longer operating time for long CMDs as compared to short CMDs, with Hong being the only dissenting study 18 , 22 31 , 33 .…”
Section: Resultsmentioning
confidence: 99%
“…Compared with cut-out, a common form of implant failure mostly occurs within 3 months postoperatively [ 25 ], IM nail breakage has a relatively late average occurrence time, but lacks of time regularity (Table 3 ; Fig. 3 ).…”
Section: Discussionmentioning
confidence: 99%